2018
DOI: 10.1186/s13148-018-0479-y
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of DFNA5 methylation reveals its potential as biomarker for breast cancer

Abstract: BackgroundBreast cancer is the most frequent cancer among women worldwide. Biomarkers for early detection and prognosis of these patients are needed. We hypothesized that deafness, autosomal dominant 5 (DFNA5) may be a valuable biomarker, based upon strong indications for its role as tumor suppressor gene and its function in regulated cell death. In this study, we aimed to analyze DFNA5 methylation and expression in the largest breast cancer cohort to date using publicly available data from TCGA, in order to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 55 publications
(51 reference statements)
3
74
0
Order By: Relevance
“…Recently, the role of GSDME in the pathogenesis of human malignancies has attracted increasing attention. Due to promoter hypermethylation, GSDME is inactivated in several cancers (24)(25)(26). Our previous studies demonstrated that chemotherapy, including 5-FU and lobaplatin, could induce pyroptosis in gastrointestinal cancer by cleaving GSDME (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of GSDME in the pathogenesis of human malignancies has attracted increasing attention. Due to promoter hypermethylation, GSDME is inactivated in several cancers (24)(25)(26). Our previous studies demonstrated that chemotherapy, including 5-FU and lobaplatin, could induce pyroptosis in gastrointestinal cancer by cleaving GSDME (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular signatures have been proven to predict the clinical prognosis in different kinds of tumors [ 6 , 10 , 30 , 31 ]. For instance, the methylation of PCDH19 predicted a poor prognosis of hepatocellular carcinoma [ 31 ]; the methylation of DFNA5 showed strong potential as a prognostic biomarker for breast cancer; and the signature of CXCL11 combined with HMGA2 could precisely predict the OS of patients with high-grade serous ovarian cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression analysis of these ten genes between high- and low-risk patients indicated that one possible reason was that mRNAs acting as biomarkers had larger fold changes in the expression level to be captured by our statistical methods. Further, it is generally believed that DNA methylation has an effect on the gene regulation with several exceptions [ 6 , 39 ]. The potential association between the methylation level and the gene expression levels of these five genes demonstrated that only the expression of SLC39A14 and CORO6 was significantly ( P < 0.05) correlated with the methylation levels at cg05254747 and cg06038133 sites, respectively, and no statistically significant association was observed between the methylation level and the expression of the other three genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition, reduced GSDME levels are associated with worse 5-year survival and increased metastases from breast cancers. 36 Chemotherapeutics, such as cisplatin, lobaplatin and doxorubicin, were shown to trigger pyroptosis in cancer cell through caspase-3dependent cleavage of GSDME. 37,38 Recently, GSDME has been found to exert a marked effect on the tumor immune microenvironment via pyroptosis.…”
Section: Gsdmcmentioning
confidence: 99%